School and prejudice: study on prejudice against geographical origin and place for teacher training - Villela, Fabio Fernandes [UNESP] (Univ Metodista Piracicaba-unimep, 2016)
This text aims at presenting some results of the research that made it possible to investigate the social representations of prejudice against geographic origin and place in students from rural schools, with the main purpose of improving teacher training (cf. AUTHOR, 2013-2015). In the context of the macro-region of Sao Jose do Rio Preto (SP), social representations of the yokels are relevant, so this project intends to collaborate in the development of relevant research in the description and understanding of processes involving the relations between prejudice, education, and the rural world, especially the traditional communities called yokels.
Keywords: SOCIAL REPRESENTATIONS; PREJUDICE AGAINST GEOGRAPHIC ORIGIN AND PLACE; TEACHER TRAINING